ZBTB17 (MIZ1) Is Important for the Cardiac Stress Response and a Novel Candidate Gene for Cardiomyopathy and Heart Failure. - Buyandelger,B; Mansfield,C; Kostin,S; Choi,O; Roberts,AM; Ware,JS; Mazzarotto,F; Pesce,F; Buchan,R; Isaacson,RL; Vouffo,J; Gunkel,S; et al. (Circulation. Cardiovascular Genetics, 2015)
BACKGROUND: -Mutations in sarcomeric and cytoskeletal proteins are a major cause of hereditary cardiomyopathies, but our knowledge remains incomplete as to how the genetic defects execute their effects. METHODS AND RESULTS: -We used cysteine and glycine-rich protein 3 (CSRP3), a known cardiomyopathy gene, in a yeast two-hybrid screen and identified zinc finger and BTB domain containing protein 17 (ZBTB17) as a novel interacting partner. ZBTB17 is a transcription factor that contains the peak association signal (rs10927875) at the replicated 1p36 cardiomyopathy locus. ZBTB17 expression protected cardiac myocytes from apoptosis in vitro and in a mouse model with cardiac myocyte-specific deletion of Zbtb17, which develops cardiomyopathy and fibrosis after biomechanical stress. ZBTB17 also regulated cardiac myocyte hypertrophy in vitro and in vivo in a calcineurin-dependent manner. CONCLUSIONS: -We revealed new functions for ZBTB17 in the heart, a transcription factor which may play a role as a novel cardiomyopathy gene.